Crime, Victims and Policy
XII, 284 p.
Keywords: This book provides critically examines how recent international developments in victims theory and policy are experienced within specific local contexts. The chapters approach key criminological issues including the experience of criminal justice agencies, policy formulation, the construction of victim identities and the 'discovery' of new victims.